Blended Learning Model During Covid-19 Pandemic to Increase Mathematics Learning Outcomes in Senior High School - Nova Erawati Sidabalok; Arif Yuandana Sinaga (AL-ISHLAH: Jurnal Pendidikan, 2021)
Distance learning requires teachers to select appropriate instructional methods to ensure that students comprehend what the teacher communicates without meeting face to face. The purpose of this study is to demonstrate how a Blended Learning model centered on two-way communication can be applied during a pandemic. This is a quantitative method of research that employs a quasi-experimental design. The research variables include the dependent variable, which is the outcome of mathematics instruction, and the independent variable for the Blended Learning model. The research design used was a pretest-posttest randomized control group design. Subjects were assigned randomly to the experimental group, administered a pretest, and received treatment using a blended learning model. Following that, the final test (posttest) was administered. Given that the final value of the test in this study is 1.712, the table value at a 0.05 significance level, and a sample size of 30 students is 1.697. The conclusion is that the value of 1.712 is greater than the 1.697 t table value. Because the value of t count is greater than the value of the t table, the criteria H0 is rejected, and Ha is accepted. The blended learning model can effectively improve students' mathematics learning outcomes.